Implementasi Desentralisasi dan Otonomi Daerah Tingkat II Masa Orde Baru - Utomo, Warsito (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 1997)
Act No. 5 of 1974 on the Principles of Administration in Indonesian Local Government stipulates fundamental effort for decentralization Ã¢â¬â or more commonly known as local autonomy. This analysis shows, however, that insofar the implementation of the government act encourages more centralization instead of decentralization. It means that the Central Government has been dominantly rules nearly all aspects of local government during the New Order period. It is obvious that the implementation of decentralization policy or local autonomy is mostly determined by the existing political system and structure. On the Second Stage of local (Daerah Tingkat II), there are various local or internal factors which appears to be very influential for the effectiveness of such policy implementation. A descriptive analysis of the two Second Stage of local governments (Cilacap and Kudus) indicates there are significant policy implementation differences. The very fact that there are local condition differences, specific handicaps confronted by local government, and some variance in human resources capability implies that the idea of uniformity in most of administrative procedure might not favourable for the future of decentralization and local outonomy policy. This is particularly important if we analyze all aspects related to such policy implementation. The above things do get sufficient attention in nearly all of this paper.